2018
DOI: 10.1063/1.5050447
|View full text |Cite
|
Sign up to set email alerts
|

Electrical field enhanced interfacial Dzyaloshinskii-Moriya interaction in MgO/Fe/Pt system

Abstract: We report electric field control of the interfacial Dzyaloshinskii-Moriya interaction (DMI) in MgO/Fe/Pt multilayers. The interfacial DMI is obtained and quantified by Brillouin light scattering measurements based on the frequency nonreciprocity of spin waves in a ferromagnet. The magnitude of the induced DMI is found to linearly increase as a function of electric field intensity. The efficiency of electric field control of the interfacial DMI characterized as a ratio of the DMI energy change to the electric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…Interfacial DMI is essential for stabilizing skyrmions in Pt/Co/Ta (see ref. 8 ), and we used Brillouin light spectroscopy (BLS) 21 , 22 to measure it under different electric fields. By measuring the wave-vector dependence of the frequency difference Δ f between the anti-Stokes and Stokes peaks, the interfacial DMI strength of the Pt/Co/Ta multilayer ( D ) can be determined by the following equation: where k is the in-plane wave vector, γ is the gyromagnetic ratio, and M S is the saturation magnetization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interfacial DMI is essential for stabilizing skyrmions in Pt/Co/Ta (see ref. 8 ), and we used Brillouin light spectroscopy (BLS) 21 , 22 to measure it under different electric fields. By measuring the wave-vector dependence of the frequency difference Δ f between the anti-Stokes and Stokes peaks, the interfacial DMI strength of the Pt/Co/Ta multilayer ( D ) can be determined by the following equation: where k is the in-plane wave vector, γ is the gyromagnetic ratio, and M S is the saturation magnetization.…”
Section: Resultsmentioning
confidence: 99%
“…The similarities in the volatility and asymmetry between interfacial DMI and strain behaviors indicate a strain-mediated electric-field control of interfacial DMI. Some reports showed importance of charge accumulation/depletion 22 or ion migration 21 in controlling Rashba-type interfacial DMI (see ref. 38 ) with a sizable modulation via electric-field gating on the dielectric/FM interface 21 , 22 .…”
Section: Resultsmentioning
confidence: 99%
“…[6] where the XY spin chain with random changes in the sign of DM interactions was studied. However, recently it has been demonstrated that DM interaction can be efficiently tailored with an substantial efficiency factor by structural modulations [24] or by external electric field [25][26][27]. This unveils the possibility not only to control DM interaction and magnetic anisotropy via the electric field or other controllable ways, but also opens a possibility to consider effect of more general spatially modulated DM interaction on properties of the spin chain.…”
Section: Introductionmentioning
confidence: 99%
“…Skyrmions are nontrivial magnetic spin textures considered to offer better functionalities for spintronic and storage devices owing to their topological nature, which provides stability from defects and from external perturbations [8][9][10][11][12]. For example, it has been shown that skyrmions and skyrmionic structures can be displaced using relatively small current densities [12], stabilized under an applied magnetic field [13] and, when interfaced with a gate dielectric, controlled by an applied electric field [14][15][16][17]. More generally, the topological nature of a spin texture is characterized by the topological charge or skyrmion winding number [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%